Lung microbiota: a new hope for treating acute respiratory distress syndrome? - Yao Tang; Bo Liu; Aijia Ma; Bo Wang; Huaiyu Xiong; Yi Zhou; Jing Yang; Yan Kang (Frontiers in Microbiology)
The lung microbiota, present in healthy individuals, undergoes alterations in different diseases and is closely linked to changes in both systemic and alveolar immunity. These interactions play a crucial role in the onset and progression of numerous diseases. Acute respiratory distress syndrome (ARDS), one of the most severe conditions encountered in intensive care units (ICU), is characterized by high incidence and mortality rates. The pathophysiology of ARDS involves complex mechanisms, including the activation and dysregulation of overlapping pathways related to injury, inflammation, and coagulation, both locally in the lungs and systemically. Notably, alterations in the microbiota may contribute to the pathogenesis of ARDS. Emerging evidence suggests that changes in the lung microbiota are associated with ARDS development, often marked by increased bacterial burden, reduced microbial diversity, and shifts in microbiota composition. In this review, we focus on the regulatory roles of the lung microbiota in ARDS and their therapeutic potential.